Changes in Gut Microbiota of Patients with Atopic Dermatitis During Balneotherapy - Thirion F; Guilly S; Fromentin S; Plaza Oñate F; Alvarez AS; Le Chatelier E; Pons N; Levenez F; Quinquis B; Ehrlich S; Doré J; Martin R; et al. (Dove Medical Press, 2022)
Florence Thirion,1,* Susie Guilly,1,* Sébastien Fromentin,1 Florian Plaza Oñate,1 Anne-Sophie Alvarez,1 Emmanuelle Le Chatelier,1 Nicolas Pons,1 Florence Levenez,1 Benoît Quinquis,1 Stanislav Ehrlich,1 Joel Doré,1,2 Richard Martin,3 Sophie Seité4 1University Paris-Saclay, INRAE, MGP, Jouy-en-Josas, 78350, France; 2University Paris-Saclay, INRAE, AgroParisTech, Micalis Institute, Jouy-en-Josas, France; 3Mercurialis Biotech, Rochecorbon, France; 4La Roche-Posay Dermatological Laboratories, Levallois-Perret, France*These authors contributed equally to this workCorrespondence: Sophie Seit&#x00E9La Roche-Posay Dermatological Laboratories, 62 quai Charles Pasqua, Levallois-Perret, 92300, France, Tel +33 1 49 64 33 40, Email sophie.seite@loreal.comIntroduction: Balneotherapy (BT) is the treatment of disease through the use of thermal spring water (TSW). It has been used for centuries and remains a popular form of treatment for dermatologic diseases such as atopic dermatitis (AD). Recent findings highlighted the role of the gut microbiota in AD and the possible crosstalk between gut and skin microbiomes in this pathology. Nevertheless, changes in the composition of the gut microbiota after balneotherapy remain to be elucidated.Methods: A total of 96 patients, with moderate to severe AD according to the SCORAD, were enrolled. Stool samples were collected prior and post a 3-week balneotherapy at the thermal care center of La Roche-Posay (France). Composition of the gut microbiota was assessed by shotgun metagenomic sequencing.Results: Species associated with high gut microbiota richness tended to correlate negatively with disease severity (SCORAD) and positively with SCORAD reduction, while species associated with low richness displayed the opposite pattern. Relative abundance of 23 species was significantly altered during BT, these changes being significantly associated with SCORAD reduction during BT, suggesting that gut microbiota composition and AD progression were associated through the treatment. Microbial functions related to gut-brain axis such as GABA and tryptophan metabolism were also altered by the treatment. Long-standing AD patients exhibited a better gut microbial profile than recently diagnosed patients, with higher MSP richness and species associated with SCORAD reduction.Conclusion: In patients with AD, clinical disease parameters such as SCORAD or disease duration are intricately linked to the gut microbiota composition. SCORAD reduction occurring during BT was also associated with gut microbiota. The gut-brain-skin axis via neurotransmitter such as GABA should be further studied in diseases such as AD.Keywords: atopic dermatitis, balneotherapy, gut microbiota, shotgun metagenomics, thermal spring water